Pentecostal urbanism?: exploring the experiences of immigrants in Johannesburg - Nyuke, Simbarashe (My University, 2021)
This study draws lessons from Rod of Authority church in Turffontein, Johannesburg to explore the role of Pentecostalism in immigrants’ experiences in and of the city. The thesis departs from much of the discourses on religion and migration that romanticize Pentecostalism as a liberating force in immigrants’ experiences in and of the city. It does so by revealing the constraining and violent dynamics of Pentecostalism on immigrants’ quest to adjust to city life which are often missed in the dominant conversations and narratives about religion and migration. The thesis is anchored in rich ethnographic research of more than twenty months of attending Rod of Authority church where I observed and analyzed the everyday lives and experiences of the congregants in and outside the church environment. I uncover the relationship between the immigrants and Pentecostalism as a complex one that is on one hand liberating and on the other hand constraining and disabling. Understanding this complex relationship requires attention to how Pentecostal theology is employed as an ideological tool to create passive subjectivities in immigrants and creates dependency on Pentecostalism as they grapple with the vagaries of the city. Pentecostal theology proffers life-sustaining practices that give congregants hope and confidence to endure and overcome but concurrently pacifies and strips off their agency. I argue that Pentecostal anointed material objects meant to embolden and enable immigrants to navigate a ‘hostile’ and ‘dangerous’ city further pushes them to depend on religious experts (i.e. pastors, prophets etc.) who have monopoly over production and distribution of such objects for security and success. Furthermore, the promises and interventions by Pentecostalism though presented as disinterested by the experts, comes at a cost. As such, I make a case for hope as a product of investment that demands the cooperation and commitment from the congregant. Following my empirical observations of the Pentecostal mediatory practices in the lives of immigrants, I argue that Pentecostalism is violent even though it manifests as an agent ofsecurity and hope. Ishow that Pentecostalism islike a double edged sword meting violence against the congregant whom it purports to serve. I further argue that Pentecostalism just like the city ofJohannesburg operates with the same logic and is violent in its dealing with the congregants. Johannesburg’s case is chosen because of its intriguing character of diverse realities of opportunities and challenges where individuals, and groups coalesce and, contest in competition to produce, acquire and access different forms of capital. Furthermore, migration from within and outside the borders of South Africa remains skewed towards Johannesburg in ways that add a layer of complexity to the city’s enigmatic character and sets it as an intriguing case to demonstrate immigrants’ experiences of city life without relying on a broad generalizing schema. I highlighted the primacy of urban Pentecostal theologies and practice in shaping the habitus of immigrant congregants’ perceptions of the city and as lens to understand how meanings are produced and then attached to the immigrants’ experiences. Insights about the lived realities and life worlds of immigrant Pentecostal adherents and a construction of a totality of meaning to immigrants’ lives and experiences through Pentecostal theology were drawn from observation, in-depth interviews, casual conversations, home and work visits where possible. By presenting the complexity of the mediatory role of Pentecostalism in immigrants’ lives, the study contributes to growing literature on religion and migration and provide clues for rethinking about the role of Pentecostalism beyond the increasingly dominant debates that depict Pentecostalism as a liberating force
A thesis submitted in fulfilment of the requirements for the Doctor of Philosophy to the Faculty of Humanities, School of Social Sciences, University of the Witwatersrand, 2021